The Marine Natural Product Mimic MHP88 Shows Anticancer Activity and has the Potential to Cause Immunogenic Cell Death - von Hofsten, Susannah; Norvoll Magnussen, Synnøve; Ausbacher, Dominik; Paulsen, Marianne Hagensen; Bayer, Annette; Strøm, Morten B.; Berge, Gerd (2020)
Conference web site at https://www.eaa2020.org/ . The marine natural product mimic MHP 88 is a novel synthetic molecule based on unique structures found in molecules from an arctic marine bryozoan. Initial studies showed that MHP88 kills cancer cells efficiently, but is not hemolytic. In this study, we look closer at the mode of death induced by MHP88 in oral cancer (HSC-3) and lymphoma (Ramos) cell lines. Immunogenic cell death (ICD) is a mode of death that can be induced by some anticancer molecules and is characterized by the release and expression of certain damage associated molecular patterns (DAMPs) which have immune stimulating effects. Specifically, the release of high mobility group box 1 (HMGB1) and ATP, as well as the translocation of calreticulin from the ER lumen to the outside of the cell membrane, constitute the major hallmarks of ICD. In vivo ICD induced in cancer cells has a vaccination effect, protecting the host from future challenge with the same cancer cells. Animal studies on the molecule LTX-401, which has similar properties as MHP88 have successfully demonstrated this effect.